From silence to recognition: Swedish social services and the handling of honor-based violence. Issue 2 (4th March 2022) - Olsson, Helén; Bergman, Ann
ABSTRACT: Societal norms and values along with laws and regulations strongly influence social work, as do megatrends as globalisation and migration. International agreements on human rights with special focus on violence against women have drawn attention to domestic violence, including honor-based violence (HBV). The purpose of this paper is to identify the factors that affect social workers' ability to work within the area of HBV and their experiences of their current work situation. Based on a qualitative approach using in-depth interviews with Swedish social workers, the study shows that HBV is not a new phenomenon in social work, but that unfamiliarity and a lack of legitimacy have made it difficult for social workers to deal with the issue. Inspired by recognition theory, a picture emerges of a profession with low mandates and low recognition that lacks resources regarding education, guidelines and a common view on how HBV should be identified and handled, both within the social workers' own organisation and in other authorities. The dynamics of HBV and approaches to the issue require a present state and legislative support. Social workers also need support from researchers in the field to develop effective interventions in their practical social work with HBV.